Understanding the Dynamics of Sulfur Droplets Formation in Lean‐Electrolyte and Low‐Temperature Lithium–Sulfur Batteries - Qi Qi; Fangyi Shi; Jingya Yu; Yiyuan Ma; Feiyang Chen; Wei Lv; Wing‐Cheung Law; Shu Ping Lau; Zheng‐Long Xu (Advanced Science)
Abstract Lithium–sulfur batteries (LSBs) afford great promises as the next‐generation rechargeable batteries due to the high energy density and low cost of sulfur cathodes. Lean‐electrolyte condition constitutes the prerequisite for high‐energy LSBs, but the insulating sulfur particles hinder capacity utilization, especially at low temperatures. Here, the electrochemical generation of liquid sulfur droplets in the LSB system are studied and elucidate the polysulfide oxidation reaction (SOR) kinetics under different electrolyte/sulfur (E/S) ratios and low‐temperature conditions. The real‐time observations under in situ optical and Raman microscopies indicate that the formation of liquid sulfur during SOR is independent of the E/S ratio and can be preserved over a wide range of operating temperatures. Quantification of the polysulfide reactant concentrations and the amounts of the liquid sulfur product under different charging conditions reveal pseudo‐zero‐order kinetics and E/S ratio‐dependent reaction constants for the SOR process. In addition, under extreme conditions of −20 °C and E/S ratio of 5 µL mg−1, liquid sulfur can still be preserved by following the rapid SOR kinetics. These findings provide new insights into the liquid sulfur generation dynamics in Li─S chemistry, which enables a deeper understanding of the effects of the E/S ratio and working temperature on the oxidation kinetics in LSBs.